The Implementation of SQ3R in Elementary School: A Quasi-Experimental Research - Uyu Mu'awwanah; M. Syahbudin; Khaerul Fajri (Prodi PGSD FKIP Universitas Islam Sultan Agung, 2026)
This study aims to examine the effectiveness of applying the SQ3R (Survey, Question, Read, Recite, Review) reading strategy in improving reading comprehension skills among elementary school students. The background of this research is based on the low reading comprehension abilities observed in students, which is evident in their difficulty in identifying key information, summarising the content of the text, and answering questions based on the reading. The research method employed is a quasi-experimental design with a pretest-posttest control group. The subjects of the study are fifth-grade students from a public elementary school, divided into an experimental group and a control group. The instrument used was a reading comprehension test. Data analysis results reveal a significant difference in the posttest scores between the experimental group and the control group. The application of the SQ3R strategy proved to be more effective in enhancing students' reading comprehension compared to conventional teaching methods. Therefore, the SQ3R strategy can serve as an innovative learning alternative to improve the literacy quality of elementary school students.